Orques tolkienesques : entre OGM et androïdes posthumains ? - Éline de Mathuisieulx (Recherches Germaniques)
Fantasy and science fiction are often intertwined, and tend to influence one another. Tolkien’s Orcs, and more specifically, his Uruk-hai, are genetically modified organisms, which are studded with metal to improve them and could have been inspired by Asimovian robots. Overall, those humanicide and sanguinary creatures are evocative of the Gothic tradition. It seems that the cinematographic adaptations by Peter Jackson, mostly based on John Howe’s illustrations, have brought their demonization to a paroxysm.